Study of buried interfaces in Fe/Si multilayer by hard x‐ray emission spectroscopy. (17th August 2021) - Verma, Hina; Le Guen, Karine; Delaunay, Renaud; Ismail, Iyas; Ilakovac, Vita; Rueff, Jean Pascal; Zheng, Yunlin Jacques; Jonnard, Philippe
Abstract : Hard x‐ray emission spectroscopy (XES) has been used to study buried layers and interfaces in a Fe/Si periodic multilayer. Until now, buried layers could be studied using the XES in the soft x‐ray range. Here, we extend the methodology to study the buried interfaces in hard x‐ray region (photon energy ≥ 5 keV). We report the formation of FeSi2 at all the interfaces with thicknesses of 1.4 nm. X‐ray reflectivity measurements enable us to deduce the structure and thickness of the multilayer stack, thereby confirming the presence of FeSi2 .